Analisis Kurikulum 2013 pada Kompetensi Inti 3 Kelas XII SMA Berdasarkan Dimensi Proses Kognitif dan Pengetahuan - Helmi Maulina Ritonga; Eka Yusmaita (Universitas Negeri Padang, 2019)
This study aims to analyze the Core Competency 3 of Curriculum 2013 12th Grade Senior High School (SMA), which are described based on Bloom’s taxonomic cognitive process dimensions and knowledge into several components. Core Competency 3 Analysis is carried out to assist the process of compiling and matching the types of cognitive and knowledge that students must possess to achieve graduate competency. This research method is descriptive qualitative with literature study data collection techniques. After the data is collected, analysis of core competency 3 is carried out to see its suitability with Bloom’s taxonomy revision based on cognitive and knowledge process dimensions. The results obtained in the form of KI-3 analysis components became 56 components, each component producing 14 components cognitive process dimension and 4 components knowledge dimension.